THE ANALYSIS OF GENDER REPRESENTATION IN LOVE, SEX, DEATH, AND WORDS SURPRISING TALES FROM A YEAR IN LITERATURE BY JOHN SUTHERLAND AND STEPHEN FENDER - Nailul Authar; Novi Rahmania Aquariza (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2020)
The aims of this study is to find out the Gender Representation in Love, Sex, Death, and Words Surprising Tales from a Year in Literature by John Sutherland and Stephen Fender and to reveal the message between them. This study uses descriptive qualitative analysis since the data are not statistically analyzed and the data of this study are picture and text, which exist in the book. The findings of this study will show that diction and gender have integrated each other. Both of them have much influence in Love, Sex, Death, and Words Surprising Tales from a Year in Literature. Finally, this study has much beneficial for those who want to know more about the way gender takes part in the book. There are several ways to make a good literature work especially in this book and one of the strategy is gender. Gender has a unique way to make literature work can be seen beautifully. Additionally, this research gives additional information for those who intend to conduct the research on the same topic but different object of the research to get varied result of the research.